The professional educational practices of the Education carrier UACJ: experiences and perspectives of the students (Praxis Educativa, 2019)
This work approaches the perceptions, experiences and interpretations of undergraduate students in the educational field about their process in Professional Educational Practices (PEP). The research is situated paradigmatically under the hermeneutic perspective, using the discovery logistic method. A survey was created which collected data about the process and experience of professional practice, in a non-probabilistic voluntary sample with students attending this stage. Data was analyzed about self-regulation of the process, about the link between the practice and the labor field and the learning constructed. As a result, it was observed that the learning acquired is favorable, self-regulation processes occur in most of the participants, and students find spaces and elements that correspond to their professional expectations and their training experience, in addition to the fact that the knowledge obtained in practice is useful to their professional future.
Keywords: professional practice; educational practice; initial teachers training; relationship theory- practice; teaching learning process